ANALISIS PENGARUH KEBIJAKAN PEMASARAN KREDIT TERHADAP PENYALURAN KREDIT PRODUKTIF PT. BANK PEMBANGUNAN DAERAH KALIMANTAN BARAT KANTOR CABANG UTAMA PONTIANAK - B31109061, Iskandar (Jurnal Manajemen Update, 2015)
This study aimed to determine the effect of credit marketing policy with the approach of marketing mix variables consist of product, price, promotion, place, people, processes, and physical evidence and to determine the policies of credit marketing the most dominant influence on the Union Bank productive lending West Kalimantan. The number of samples can be determined by 110 people debtor. Collecting data using questionnaires, interviews and documentation. The data analysis technique used is the technique of multiple regression analysis. Data processing was performed using SPSS which after processing the data to obtain information about the characteristics of the phenomenon then testing the effect to explain the relationship between the phenomena tested. The first test to be performed is validatas and reliability test on the questionnaire as a measurement tool in this study. Then do the Classical Assumption Test consisting of Normality Test, Multicollinearity, heterokedastisitas and linearity before performing multiple regression analysis test. After that is done and the Partial Test Effect of Simultaneous Effect. Results of research conducted indicates that the product, price, promotion, place, people / employees, process and physical evidence of a positive and significant effect on lending productive and influential variables most to credit is a variable price in this case the interest rate credit Keywords: Product, Price, Promotion, Place, People / Employee, Process, Physical Evidence